Evaluation of the correlations between the normalized difference vegetation index (NDVI) and yield in a seasoning paprika (Capsicum annuum L. var. longum) stand - Dobos, Attila; Víg, Róbert; Nagy, János; Takácsné Hájos, Mária (Acta Agraria Debreceniensis, 2014)
The aim of our examination was to evaluate the correlations between the normalized difference vegetation index (NDVI) and yield, as well as to examine the possibility of yield estimation basedon NDVI in a seasoning paprika population.Significant correlations were observed during the examination of the correlation between NDVI and yield. Furthermore, it was concluded that yield can be estimated with a 6.6–8.3% mean error based on the regression equations. No significant difference was shown between the error of estimations performed with various regression types and that of the estimations performed at various dates. For this reason, the identification of the optimum estimation method and the determination of the optimum date for estimation call for further examinations.